Validation of an experimental setup for creating augmented acoustic environments (Student Conference Proceedings, 2025)
This study aimed to validate calibration routines for an experimental setup that simulates and presents realistic acoustic environments via open headphones, with real-time motion tracking. A virtual acoustic environment was implemented, using the real-time SimulatedOpen Field Environment (rtSOFE) software package, which employs the image source method for real-time applications. This setup, including a set of calibration filters and the procedures to create them, was previously used to study face-to-face communication in nosy environments. The results in the present work support the use of this system and it’s filter creation procedures in future auditory research, providing a reliable platformfor real-time experimentation in virtual and augmented acoustic environments.
Keywords: Augmented Acoustic Environment; Binaural Room Impulse Response